In silico Characterization of UGT74G1 Protein in Stevia rebaudiana Bertoni Accession MS007 - Khan, Afiqah Rahmatullah; Mokhtar, Nor Iwani; Zainuddin, Zarina; Samsulrizal, Nurul Hidayah (Journal of Tropical Life Science, 2021)
Stevia rebaudiana is being promoted as an alternative sweetener in particular for diabetic and obese patients due to its low-calorie property. The steady demand in the market for high-quality stevia extracts presents a challenge for enhanced production of steviol glycosides that are safe for human consumption. This study characterized the structure and content of gene involved in the production of UGT74G1 protein for S. rebaudiana accession MS007 through in silico analysis using transcriptome dataset of stevia MS007.Â  Homologous search using BLASTp show high similarity to Q6VAA6 RecName: Full=UDP-glycosyltransferase 74G1 (S. rebaudiana) as the top hit sequences. InterPro family and domain protein motif search revealed the presence and entry of IPR002213 and IPR035595. The construction of the phylogenetic tree was done by selecting 19 out of 102 protein sequences from BLASTp. The phylogenetic analysis showed the same protein family which is Asteraceae. ProtParam Ex-Pasy, PSIPRED and Phyre2 computed the primary, secondary, and tertiary structures for UGT74G1 protein. The UGT74G1 predicted tertiary structure scored 100.0% confidence by the single highest scoring template and coverage of 96%. The model has dimensions (Ã…) of X: 57.609, Y: 70.386, and Z: 58.351. Outcomes of this research will help to enhance the understanding of UDP-glycosyltransferase 74G1 (S. rebaudiana MS007) characteristic and enhance target identification processes to improve understanding of protein-protein interaction in S. rebaudiana MS007.